ANALISIS RESIKO USAHA DENGAN LEAN START UP MASA PANDEMI COVID-19 PADA AKUN MEDSOS MAXIMALLFOOTWEAR - Rismawati Rismawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Lean Startup is a method for developing products and businesses in a short time. The form of the research method that will be used is qualitative research. From the results of this study, it shows what has been done by MAXIMALLFOOTWERE in conducting business processes digitally and what is the effect of the processes taken by the company to improve business efficiency. In addition, MAXIMALLFOOTWEAR also still needs to improve its management performance by considering some better ideas. Therefore, it is important for lean startups to improve the company's internal systematics, it is very necessary and improved in order to increasingly provide better services. Therefore, the MAXIMALLFOOTWEAR company still needs to improve its business efficiency and effectiveness from customer support to its production process which needs to be improved by considering the feedback obtained from customers.